An Analysis of Adjective-Related Errors Made by Jordanian EFL Students - Assaf , Marouf Muhammad (Dirasat: Educational Sciences, 2023)
Objectives: This study investigates the adjective-related errors that Jordanian EFL students make in their speech and writing. Methods: Based on the researcher's observation record of his students' spoken and written assignments from the eighth to twelfth grades, the researcher compiled a list of adjective-related errors that were common among his students. To find out whether such errors were generalizable nationwide, 252 English language teachers, who were randomly selected, completed a five-point Likert-scale questionnaire by marking how often their students committed each adjective-related error. Results: The study showed that there were seven adjective-related errors commonly made by students, and such errors can be generalizable nationwide. The most common error was the use of adjectives with wrong prepositions. Among the potential sources of the seven errors were first language interference, failure to apply the rule completely, and intralingual overgeneralization of the rule. Conclusions: One the areas that requires special attention by Jordanian students is the use of adjectives. Assisting students to identify the causes of the adjective-related errors and laying more emphasis on using adjectives in meaningful contexts are instrumental in dealing with such linguistic errors.